Comparing global positioning system and global navigation satellite system measures of team-sport movements - Jackson, B. M.; Polglaze, T.; Dawson, B.; King, T.; Peeling, P. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To compare data from conventional global positioning system (GPS-) and new global navigation satellite system (GNSS-) enabled tracking devices and to examine the interunit reliability of GNSS devices. Methods: Interdevice differences between 10-Hz GPS and GNSS devices were examined during laps (n=40) of a simulated game circuit and during elite hockey matches (n=21); GNSS interunit reliability was also examined during laps of the simulated game circuit. Differences in distance values and measures in 3 velocity categories (low <3 m/s; moderate 3-5 m/s; and high >5 m/s) and acceleration/deceleration counts (>1.46 and <-1.46 m·s-2) were examined using 1-way analysis of variance. Interunit GNSS reliability was examined using the coefficient of variation (CV) and intraclass correlation coefficient. Results: Interdevice differences (P<.05) were found for measures of peak deceleration, low-speed distance, percentage of total distance at low speed, and deceleration count during the simulated game circuit and for all measures except total distance and low-speed distance during hockey matches. Interunit (GNSS) differences (P<.05) were not found. The coefficient of variation was below 5% for total distance, average and peak speeds and distance and percentage of total distance of low-speed running. The GNSS devices had a lower horizontal dilution of precision score than GPS devices in all conditions. Conclusions: These findings suggest that GNSS devices may be more sensitive than GPS devices in quantifying the physical demands of team-sport movements, but further study into the accuracy of GNSS devices is required.